The Conversational Circle : Rereading the English Novel, 1740-1775 - Schellenberg, Betty A. (Book collections on Project MUSE., 1996)
Twentieth-century historians of the early novel, most prominently Ian Watt, Mikhail Bakhtin, and Terry Castle, have canonized fictions that portray the individual in sustained tension with the social environment. Such fictions privilege a strongly linear structure. Recent reexaminations of the canon, however, have revealed a number of early novels that do not fit this mold. In The Conversational Circle: Rereading the English Novel, 1740-1775, Betty Schellenberg identifies another kind of plot, one that focuses on the social group - the "conversational circle"--As a model that can affirm traditional values but just as often promotes an alternative sense of community. Schellenberg offers a model for exploring a range of novels that experiment with narrative patterns